1038. Edwardsiella tarda Bacteremia: Epidemiology, Clinical Features, and Outcomes. (26th November 2018) - Kamiyama, Shinya; Kuriyama, Akira; Hashimoto, Toru
Abstract: Background: Edwardsiella tarda is primarily associated with gastrointestinal disease, but an increasing number of cases with extraintestinal disease have been reported. Additionally, E. tarda bacteremia (ETB) may be associated with high mortality; however, little is known about its clinical epidemiology. Methods: We collected all clinical information of ETB patients identified between January 2005 and December 2016 from their electronic medical records. We described the epidemiology, clinical features, and 30- and 90-day mortality of these patients. Results: A total of 182, 668 sets of blood cultures were obtained during the study period, of which 40 sets (0.02%) taken from 26 patients were E. tarda positive. Twenty-six patients (13 men and 13 women) with a median age of 75 years were diagnosed with ETB. Clinical diagnoses by infection site included cholangitis ( n = 9), liver abscess ( n = 6), enterocolitis ( n = 4), cholecystitis ( n = 3), and spontaneous bacterial peritonitis, mycotic aneurysm, necrotizing fasciitis, empyema, osteomyelitis, and secondary peritonitis ( n = 1 each). The overall 30-day and 90-day mortality rates of ETB in our cohort was 11.5% (3/26) and 26.9% (7/26), respectively. There was no seasonal variation in the incidence of E. tarda infection. All E. tarda strains isolated from blood cultures were susceptible to all tested antibiotics. Additionally, hepatobiliary infection was more frequently seen in ETB compared with non-bacteremic E. tarda infections. Conclusion: This study is the largest case series on ETB to date. We found that ETB is a rare entity that is not associated with high mortality. Hepatobiliary infection is the most common clinical manifestation. Disclosures: All authors: No reported disclosures.